2011
DOI: 10.1080/17458080.2010.509873
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterisation and activity evaluation of CaCO3/ZnO photocatalyst

Abstract: The photocatalyst CaCO 3 /ZnO with high activity was prepared by coprecipitation method using (NH 4 ) 2 CO 3 , Zn(NO 3 ) 2 and Ca(NO 3 ) 2 as raw materials. The photocatalyst was characterised by X-ray powder diffraction, terephthalic acid photoluminescence probing technique (TA-PL), UV-vis diffuse reflectance spectroscopy and the fluorescence emission spectra. The photocatalytic activity of the photocatalyst was evaluated by photocatalytic oxidation of methyl orange and rhodamine B. The results showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…The combination of ZnO with lower CaCO3 can increase activity as the crystal size decreases. Similar results were reported that CaCO3-ZnO with a mole ratio of 1:2 has better activity 19 compared to the mole ratios 1:1 and 2:1. The crystal size of CaCO3-ZnO was increased after being modified with Y-zeolite.…”
Section: Xrd Characterizationsupporting
confidence: 88%
See 2 more Smart Citations
“…The combination of ZnO with lower CaCO3 can increase activity as the crystal size decreases. Similar results were reported that CaCO3-ZnO with a mole ratio of 1:2 has better activity 19 compared to the mole ratios 1:1 and 2:1. The crystal size of CaCO3-ZnO was increased after being modified with Y-zeolite.…”
Section: Xrd Characterizationsupporting
confidence: 88%
“…CaCO3-ZnO nanocomposites were synthesized using the coprecipitation method with modification 19 . CaCO3-ZnO nanocomposites (mole ratio 1:1) were prepared by mixing 50 mL calcium acetate 1 M and 50 mL zinc acetate dihydrate 1 M until homogeneous.…”
Section: Synthesis Of Caco3-zno Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the minor CaCO 3 phase in the 30Fe/QES photoactive material may promote the effective separation of the photogenerated electrons and holes, similar to another research work that indicated the improved photocatalytic degradation efficiencies of aqueous organic dyes (rhodamine B and methyl orange) over CaCO 3 /ZnO. 58 Furthermore, the 30Fe/QES was subjected to subsequent 2-CP removal runs without purication/ regeneration processes. It was found that the 30Fe/QES catalyst can be effectively reused, giving 2-CP removal efficiencies of 70.5% ± 0.99 in the 3rd cycle.…”
Section: Photocatalytic Efficiency and Reusabilitysupporting
confidence: 59%
“…Amidst numerous treatment processes employed to treat the textile dyeing effluents, heterogeneous photocatalysis emerges as the best, because it is a costeffective treatment process [10][11][12][13]. In the previous decade, many metal oxide semiconductors like TiO 2 , ZnO, and NiO were used as heterogeneous photocatalysts.…”
Section: Introductionmentioning
confidence: 99%